Tasawuf Enterpreneurship dalam Pengelolaan Desa Wisata Sembungan-Dieng - Sochifah Diyah Puspitasari (Journal of Sufism and Psychotherapy, 2022)
The tourism sector is an alternative in improving the welfare of a community. It's just that in the process often what happens rubs against religious norms and values, especially Islam. Therefore, in the management of a tourism object, an Islamic approach, which in this context, the concept of entrepreneurship Sufism, can be an option in anticipating these various impacts. Using this type of qualitative field research with a phenomenological approach, this article tries to explore how the implementation of entrepreneurial Sufism in the management of the Sembungan-Dieng tourist village. The results of this study found that the management of the Sembungan Dieng tourist village is based on the main concepts of entrepreneurship Sufism, namely takhalli, tahalli, and tajalli. Takhalli is realized by LMDH Giri Tirto by making Sembungan Village clean of immoral practices and things that are seen as socially negative. Tahalli is applied by maintaining the local wisdom they have. The local wisdom that exists in the Sembungan community has indeed taught nobility and how to interact with fellow human beings. Tajalli they do with two forms of innovation, namely innovation for external benefit (tourists) and innovation for internal benefit (the Sembungan village community). All three are carried out in the context of realizing mutual prosperity in accordance with the corridors of Islamic teachings.